Acute appendicitis in Ethiopia: A systematic review and meta-analysis - Aynalem Adu; Yeneabat Birhanu (Elsevier, 2021)
Background: Acute appendicitis (AA) is the most common cause of acute inflammation in the right lower quadrant of the abdominal cavity and emergency abdominal surgery. In Ethiopia, the prevalence of acute appendicitis reported is variable. This systematic review and meta-analysis is aimed to find the pooled prevalence of Acute Appendicitis in Ethiopia. Methods: The databases for the search were Pub Med, Web of Science, and Google Scholar by the date 11/03/2020. To assess publication bias, Egger's test regression analysis were applied. Subgroup analysis was conducted based on the study population and region. Results: This meta-analysis included a total of 15 studies with 6886 study subjects. The pooled prevalence of acute appendicitis was 46.95 % (95% CI, 41.62 to 52.28 %). Based on the subgroup analysis, the Tigray region ranked first (51.98 %), followed by Addis Ababa (49.35%), and the lowest prevalence of appendicitis is reported from Oromia region (47.57%). Conclusion: In this finding, the pooled prevalence of acute appendicitis was considerable. Thus, efforts should made to ensure the prevention of acute appendicitis by close monitoring of the patient prognosis and appropriate prevention techniques.